2005
DOI: 10.1159/000086894
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of aneuploidy induction in human oogenesis and early embryogenesis

Abstract: The mechanisms of aneuploidy induction in human oogenesis mainly involve nondisjunction arising during the first and second meiotic divisions. Nondisjunction equally affects both whole chromosomes and chromatids, in the latter case it is facilitated by “predivision” or precocious centromere division. Karyotyping and CGH studies show an excess of hypohaploidy, which is confirmed in studies of preimplantation embryos, providing evidence in favour of anaphase lag as a mechanism. Preferential involvement of the sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(62 citation statements)
references
References 109 publications
(63 reference statements)
4
57
0
Order By: Relevance
“…We also considered the alternative possibility that a small proportion of cells from the three patients might contain an extra maternal X chromosome (47,XXY) bearing a wild-type IDS allele, as a consequence of either mitotic non-disjunction or 'anaphase lag' [Delhanty, 2005]. Malsegregation of the X chromosome is known to occur at a relatively high frequency [Carere et al, 1999].…”
Section: Discussionmentioning
confidence: 99%
“…We also considered the alternative possibility that a small proportion of cells from the three patients might contain an extra maternal X chromosome (47,XXY) bearing a wild-type IDS allele, as a consequence of either mitotic non-disjunction or 'anaphase lag' [Delhanty, 2005]. Malsegregation of the X chromosome is known to occur at a relatively high frequency [Carere et al, 1999].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies analyzing human metaphase II oocytes with either CGH-FISH or CGH showed aneuploidy rates as high as 40-60% [44]. Aneuploidy rates in human embryos have been reported to vary between 15-85% [28].…”
Section: Discussionmentioning
confidence: 99%
“…It has been argued that the first few cell division cycles during early embryonic development may be particularly sensitive to mitotic errors when all the necessary cell cycle check points are not activated and maternal cytoplasmic factors are needed during the early phase of embryonic development [44,49,50]. The relationship between the mix of cells that are diploid/ aneuploidy and diploid/mosaic and of their ability to develop to morphologically normal appearing blastocysts is not well established, although chaotic mosaics display high rates of developmental arrest [28,51].…”
Section: Discussionmentioning
confidence: 99%
“…Most recently it has been suggested that the maternal age effect is a multifactorial trait, and may be influenced by environmental factors ( 8,9 ). Another intriguing possibility it that normal women may be trisomy 21 ovarian mosaics ( [11][12][13] with the potential for oocytes containing three chromosomes 21 accumulating during maturation and when reaching MI undergoing obligatory secondary non-disjunction at AI.…”
Section: Linkage Analysis Of Trisomy 21mentioning
confidence: 99%